Usability Testing Method: Efisiensi, Efektivitas dan Kepuasan Pengguna Terhadap Website SMKN 1 Praya - Muhammad Zamroni Uska; Usuluddin Usuluddin; Siti Sriatni (Jurnal Pendidikan Informatika (EDUMATIC), 2019)
This research aimed to know the level of efficiency, effectiveness, and satisfaction for users of the website of SMKN 1 Praya using the usability testing method. This research was quantitative descriptive. The populations were all students and teachers at SMKN1 Praya which consisted of 1543 people. The samples were 10 people. The technique of data collection of this research used Performance Measurement, Retrospective Think Aloud (RTA), documents, and SUS questionnaires (questionnaire). This research showed that the level of the efficiency on the website of SMKN 1 Prayawhich was measured by the man Whitney u-test obtained 1 â‰¤ 2 results so that the website of SMK 1 Praya was categorized inefficient. The effectiveness of the website at SMKN 1 Praya had been effective with success results of 88.3%. Furthermore, the level of satisfaction of users of website of Praya SMKN 1 was good category with a score of SUS score was 69.1â‰¥68 with grade B. Based on the result of this research, the researcher Recommend the improvement of the website of SMKN 1 Prayaon case display the information of the school data completely and the school activities to support the learning process.